THE PROBLEM OF MALARIA AND ITS ERADICATION IN THE EXTREME SALIENT OF JAVA DURING THE DUTCH COLONIAL ERA - Nawiyanto Nawiyanto (Paramita: Historical Studies Journal)
The extreme salient of Java has often been described as ‘malarious land’ and ‘unheathy region’. Although it had a great consequences on the people’s conditions of health and socio-economy, the problem of malaria has rarely been well-understood and fairly-treated in the existing historical studies. This paper is expected to fill in the existing gap in our knowledge on the issues. By using the available historical sources, the paper seeks to elaborate the problem of malaria and its eradication efforts in the extreme salient of  Java during the Dutch colonial era. The major objectives of the paper are to examine the seriousness of malaria problem existing in the region and its causes, and to elaborate the ways in which the problem of malaria was contained by the colonial authorities. It is argued that there was a significant progress in the fight against malaria and the understanding of the malaria causes and the chosen methods of eradication reflected both scientific advances and economic considerations.